2024
DOI: 10.1136/oemed-2023-108976
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic inequalities among NHS staff in England: workplace experiences during the COVID-19 pandemic

Rebecca Rhead,
Lisa Harber-Aschan,
Juliana Onwumere
et al.

Abstract: ObjectivesThis study aims to determine how workplace experiences of National Health Service (NHS) staff varied by ethnicity during the COVID-19 pandemic and how these experiences are associated with mental and physical health at the time of the study.MethodsAn online Inequalities Survey was conducted by the Tackling Inequalities and Discrimination Experiences in Health Services study in collaboration with NHS CHECK. This Inequalities Survey collected measures relating to workplace experiences (such as personal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…NHS staff from ethnic minority groups were more likely than white British colleagues to face workplace harassment, discrimination, and unavailability of personal protective equipment (PPE) during the covid pandemic, a study reported 6. Researchers analysed responses of 4622 NHS staff from 18 trusts to a survey by the Tackling Inequalities and Discrimination Experiences in Health Services (TIDES) group and the NHS CHECK study.…”
Section: Race Equalitymentioning
confidence: 99%
“…NHS staff from ethnic minority groups were more likely than white British colleagues to face workplace harassment, discrimination, and unavailability of personal protective equipment (PPE) during the covid pandemic, a study reported 6. Researchers analysed responses of 4622 NHS staff from 18 trusts to a survey by the Tackling Inequalities and Discrimination Experiences in Health Services (TIDES) group and the NHS CHECK study.…”
Section: Race Equalitymentioning
confidence: 99%